Banjar Economic Platform (BEP) Model: Integrating Local Wisdom into Digital Economic Literacy in Economic Learning - Muhammad Rahmatullah; Edy Suryanto; Ananda Setiawan; Dwi Atmono; Alfi Fadhilah Hakim Hrp; Rizal Iskandar; Okta Selik Ramadhan; Hafid Febriansyah (Borneo Research and Education Center, 2026)
Economic literacy among high school students remains critically low, as evidenced by test scores falling far below national and regional expectations in South Kalimantan. This issue stems from abstract, non-contextual learning models and globalization, which gradually erodes traditional local economic wisdom. This study aims to develop and describe the design of the Banjar Economic Platform (BEP), an integrated digital platform that documents the Banjar economic lexicon and serves as a culturally responsive economics learning resource. Adopting a Research and Development (R&D) methodology guided by the ADDIE model, this study involved 35 purposively selected participants, including native Banjar speakers (N=3), media and subject matter experts (N=4), and high school economics teachers (N=28). Data were collected via semi-structured interviews and structured questionnaires, then analyzed using a sequential mixed-methods approach. The needs analysis revealed that incorporating the Banjar economic lexicon (e.g., bajajak, basawah, maadati, baulah, basambat, and maulah) is highly relevant for making abstract economic concepts meaningful. Expert media validation yielded an overall Aiken’s V coefficient of 0.89, falling into the